Penyuluhan Pencegahan Penularan COVID-19 di Lingkungan Kantor dan Pembuatan Lemongrass Coolant melalui Live Zoom - Choiriyah, Nurul Azizah; Devi, Ika Mariani Ratna; Sanjaya, Sonia Anggun; Dewi, Irra Chrisyanti; Rahmah, Latifahtur (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
In the new normal era, many company leaders have restarted their business places for economic turnaround. The workplace has a major contribution to the spread of COVID-19 so efforts need to be made to break the chain of transmission. The workplace is a gathering place for a number of working populations and mobility is so high, work activities also lead to worker interaction. This community service aims to giving knowledge how to prevent COVID-19 transmission in office or industry and giving knowledge how to make beverage rich in antioxidant and vitamin C to boost immune system. This community service consists of several steps including the preparation step which includes determining the time for the implementation of counseling, making material modules, making flyers and distributing flyers. The next step is the implementation step which includes the delivery of material, questions and answers regarding extension materials and demonstrations of making Lemongrass Coolant. The implementation step was done by zoom online media the final step of this activity is evaluation by filling the questions using Google Form. The participants were 41 people who work as lecturer, human resources department, undergraduate students, government employees, etc. Prevention of COVID-19 transmission is carried out by complying with the guidelines for the Decree of the Minister of Health of the Republic of Indonesia Number HK. 01.07/MENKES/328/2020. Making Lemongrass Coolant as a healthy drink rich in antioxidants as an immune booster does not require expensive ingredients and is also easy to manufacture. The participants joined in this community service with enthusiasm as evidenced by the many questions asked to the speakers.DOI:Â https://doi.org/10.26905/abdimas.v6i1.4865